Linen monitoring using rfid for UTAR Hospital - Lau, Zhi Sen (2025)
This project explores the application of Radio Frequency Identification (RFID) technology to enhance linen management in a hospital. It introduces a semi-automated system to enhance the efficiency and accuracy of linen handling and tracking. The system integrates RFID readers and a backend server to track and identify linen items in real time. It has a simple interface that makes the linen handling process easy to use, even for users with different educational levels. Throughout the development process, the project progressed from literature review and research to prototype implementation and testing. Despite the difficulties in the form of hardware limitations and the limited resources available, an RFID-based linen monitoring fully functional prototype was established. The system is able to read RFID tag data, process it through the server, and depict key information to enable improved monitoring and decision-making. Testing confirmed that the system accurately detects, tracks, and manages linen items in a controlled environment, thereby confirming its feasibility for real-world deployment. This achievement demonstrates a practical and scalable solution for improving hospital linen operations. The project is expected to be completed within eight months to support timely deployment in a healthcare setting.